Natural variations in expression of regulatory and detoxification related genes under limiting phosphate and arsenate stress in Arabidopsis thaliana - Shukla, Tapsi; Kumar, Smita; Khare, Ria; Tripathi, Rudra D.; Trivedi, Prabodh K. (Frontiers in Plant Science, 2015)
Abiotic stress including nutrient deficiency and heavy metal toxicity severely affects plant growth, development, and productivity. Genetic variations within and in between species are one of the important factors in establishing interactions and responses of plants with the environment. In the recent past, natural variations in Arabidopsis thaliana have been used to understand plant development and response towards different stresses at genetic level. Phosphorus (Pi) deficiency negatively affects plant growth and metabolism and modulates expression of the genes involved in Pi homeostasis. Arsenate, As(V), a chemical analogue of Pi, is taken up by the plants via phosphate transport system. Studies suggest that during Pi deficiency, enhanced As(V) uptake leads to increased toxicity in plants. Here, the natural variations in Arabidopsis have been utilized to study the As(V) stress response under limiting Pi condition. The primary root length was compared to identify differential response of three Arabidopsis accessions (Col-0, Sij-1 and Slavi-1) under limiting Pi and As(V) stress. To study the molecular mechanisms responsible for the differential response, comprehensive expression profiling of the genes involved in uptake, detoxification and regulatory mechanisms was carried out. Analysis suggests genetic variation-dependent regulatory mechanisms may affect differential response of Arabidopsis natural variants towards As(V) stress under limiting Pi condition. Therefore, it is hypothesized that detailed analysis of the natural variations under multiple stress conditions might help in the better understanding of the biological processes involved in stress tolerance and adaptation.